A5 6 The Power of the TARDIS - Morriss, Luke; Matkin, Eleanor; Shkullaku, Marin (Physics Special Topics, 2023)
This paper calculates the energy required to move the Earth into its orbit around the Sun, as occurs in the 2008 Doctor Who episode “Journey’s End”. We find that 5.642 × 10^34 J of energy is required to move the Earth into its orbit around the Sun, which, when considering the energy of the TARDIS, is more than enough energy to accomplish this.